DIGOXIN AS A RESCUE DRUG IN INTRA AORTIC BALLOON PUMP AND INOTROPE DEPENDENT PATIENTS - Naqvi, Shahab; Ahmed, Iftikhar; Siddiqi, Rashad; Hussain, Syed Aqeel (Journal of Ayub Medical College Abbottabad, 2010)
Background: In absence of cardiac transplant program in our country, when patients with poor left ventricular (LV) functions undergo coronary revascularisation surgery, they are on one or more inotropic supports with intra aortic balloon pump (IABP) at the time of weaning off from cardiopulmonary bypass (CPB). Post-operatively, due to the poor LV function, many of these patients become dependent on inotropic supports and IABP and eventually have a poor outcome. We used digoxin in these patients as a rescue drug, where more than one attempts to wean them off IABP and inotropic support had failed. Objective of the study was to evaluate the efficacy of digoxin as a rescue drug in intra-aortic balloon pump (IABP) and inotropic support-dependent, post-CABG patients in terms of improvement in their left ventricular ejection fraction (LVEF), serum lactate and mixed venous oxygen saturation. Methods: It is a descriptive case series conducted at Department of Cardiac Anesthesia & Intensive Care, Armed Forces Institute of Cardiology and National Institute of Heart Diseases, Rawalpindi, Pakistan, from 1 Nov 2002 to 31 Dec 2007. Thirty post-coronary re-vascularisation patients who were inotrope and IABP dependant and could not be weaned off from supports were given a trial of digoxin to see any improvement in the cardiac functions. Mixed venous oxygen saturation (SvO2), serum lactate levels and left ventricular ejection fraction (LVEF) in the bed side echo were monitored at predigoxin stage and then at three intervals: at serum digoxin level of up to 0.5 Î·g/ml; then up to 1.0 Î·g/ml and then up to 1.5 Î·g/ml. Paired sample t-test was applied and 2-tailed significance was calculated. Results: Significant improvement was seen in the mean SvO2, serum lactate levels and LVEF when patient’s serum digoxin level were around 1.5 Î·g/dL. Clinically, 20 out of 30 patients (66.67%) improved with digoxin administration and were ultimately weaned off from IABP and inotropic supports. There was no significant correlation between patient’s improvement and presence of diabetes mellitus or hypertension. However, pre-operative IABP placement had a significant correlation as 6 out of 8 patients (75%) were successfully weaned off at digoxin levels around 1.5 Î·g/mL. Conclusion: Improvement in significant number of patients suggests that digoxin can be used as a rescue drug in IABP and inotropic support dependent patients after CABG surgery especially in countries where heart transplant program does not exist. However, more clinical trials with larger sample size are recommended for further evaluation. Keywords: Digoxin, CABG, IABP-dependent, Inotrope-dependent